2008
DOI: 10.1097/id.0b013e318177784a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Cancellous Block Allograft for Ridge Augmentation and Implant Placement: A Case Report

Abstract: A number of grafting materials have been used in vertical and horizontal ridge augmentation to enable implant placement in optimal positions. Autogenous block grafts from intraoral or extraoral sites have been used with positive results. Allograft blocks with cortical bone are also used for ridge augmentation. In this case report, a cancellous allograft block was used for horizontal augmentation of the maxilla. The observed increase in ridge width allowed subsequent implant placement after a 5 month healing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…38,39 Therefore, FFB possesses necessary strength and rigidity to allow stable fixation in the recipient area. 40 A systematic review 41 included nine studies, [42][43][44][45][46][47][48][49][50] but excluded the ones that examined freshfrozen allografts. They were mainly case reports and case series describing the outcomes of freeze-dried allografts, and eight out of them used barrier membranes.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Therefore, FFB possesses necessary strength and rigidity to allow stable fixation in the recipient area. 40 A systematic review 41 included nine studies, [42][43][44][45][46][47][48][49][50] but excluded the ones that examined freshfrozen allografts. They were mainly case reports and case series describing the outcomes of freeze-dried allografts, and eight out of them used barrier membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CHBB alone has shown a good outcome in partial bone augmentation. The outcome of CHBB alone in wide vertical ridge augmentation cannot be predicted because most previous studies have been conducted in the narrow area of the anterior maxilla 11,22 and for partial lateral ridge augmentation. In the present study, CHBB had a beneficial effect on new bone formation and the maintenance of the grafted area regardless of the application methods.…”
mentioning
confidence: 98%
“…Not only did the authors find the graft successful (allowed implant placement) but they suggested "cancellous block allografts could be a promising alternative to autogenous block grafts." Wallace and Gellin [72] reached the same conclusion when they followed this initial study up with a published 12 patient case series in 2010 that also had a 100% graft success rate (no grafts were lost by 5 months following placement). The authors also had a 100% implant success rate as "no implants failed during the 4 month integration period."…”
Section: Clinical Studies Using Og Bone Allograftsmentioning
confidence: 69%
“…The authors also had a 100% implant success rate as "no implants failed during the 4 month integration period." Wallace [73] recently published a study utilizing cancellous particulate FDBA in combination with a membrane composed of decellularized dermis to preserve extraction sites for implant placement in six patients. Histologic analysis showed a "significant percentage [average 12.8%] of new bone regeneration after 12 weeks in molar extraction sites.…”
Section: Clinical Studies Using Og Bone Allograftsmentioning
confidence: 99%